Creating mixed-income neighborhoods through middle housing infill development: a case study of St. Louis - Wackerla, Lance (Kansas State University, 2024)
Infill development, missing middle housing, and mixed income neighborhoods have continued to be prevalent topics in American city planning and have only become increasingly more predominant topics in the past decades. Each type of development sets out to address a specific set of problems by offering unique solutions such as reinvestment, diverse housing form, or diverse housing stock. While these solutions can work on their own, for many Midwest cities in the United States homogeneous housing stock and lack of more affordable housing creates pressures on lower income populations and contributes to income segregation. Previous studies on both infill housing and middle housing have shown that the implementation of these developments can have positive effects on income mixing. Few studies have analyzed the impact of combining infill development and middle housing and whether their impact together makes a difference on the distributions of income strata. This study explores the connection between infill middle housing and income mixing through a case study of the City of St. Louis, as it is not only one of the fastest declining Midwest cities in terms of population, but also has a history of segregation and a fair amount of middle housing stock. By analyzing population and unit density levels from the 2010 ACS at the block group level, calculating indexes of income variation in 2019, and applying geospatial and statistical analysis, areas exhibiting certain attributes were tested for significance in the levels of income mixing. Ultimately what was found was that areas with new middle housing developments experienced significant increase in income mixing, and when they are combined with infill developments (i.e. already dense areas), their contribution is similar.
Keywords: Middle housing; Infill development